Estudo dos sistemas aquosos bifásicos formados por polietilenoglicol e sais de tartarato, e purificação da lectina ConBol obtida a partir da Canavalia boliviana - Pinto, Alexandra Cristini Gonçalves (2016)
Purification of protein extracts is a complex process that involves several steps ranging from protein precipitation by salt solutions to chromatographic separation methods. This methodology, although well established in the scientific community, is high cost, high uptime and finds it difficult to be expanded on an industrial scale . It is in this context that the aqueous two-phase systems emerge as an economically viable and sustainable alternative, from an environmental point of view. For this study were developed two research fronts, divided in chapters 4 and 5 in this work. At fourth one was evaluated the effect of temperature, polymer molecular weight and the cation on the phase equilibria of the system formed by PEG3350 + potassium tartrate + H2O, PEG10000 + potassium tartrate + H2O and PEG20000 + potassium tartrate + H2O in pH7 and 288K, 298K and 308K. . The results show that the increasing of temperature, the increasing of polymer’s molecular weight and the cation of lower hydration energy, shifted the bimodal toward the origin, where is found lower values of concentration of Polyethyle glycol (PEG) and salt. In the fifth chapter we determined the partition coefficient (Kp), recovery rate (Y) and purity (PHPLC) of ConBol protein in systems formed by PEG400 + KH2PO4 / K2HPO4 + H2O + PEG600 and KH2PO4 / K2HPO4 + H2O. With the results it is observed that the best system to partition the ConBol protein is formed by PEG400 + KH2PO4 / K2HPO4 + H2O, in concentrations of 16%, 18.8% and 65.2% respectively. This system showed a partition coefficient (Kp) of 13.40, a recovery yeld (Y) of 6.42% and a purity of 69%.